(untitled) (Journal of Vishwa Adarsha College, 2024)
The research study aimed to explore the perceptions and practices of using the Padlet application in the secondary English language classroom. The research participants of this study included ten secondary-level learners from one of the reputed schools in Itahari Sub-Metropolitan City, Nepal, out of whom five were boys and five girls. The data/narratives were collected through the help of semi-structured interviews. The Narrative inquiry was taken as the research method for the study. A purposive sampling technique was used to choose the representatives who were familiar with using the Padlet application. The data was analyzed by drawing common themes from the narratives. The findings of the study demonstrated that learners felt positive while using the Padlet application in their classroom. It showed the various significance of Padlet which could foster the level of learners in different ways. The research study explored the significance of using the Padlet application in improving writing skills, collaboration, and teamwork, raising interest, fostering digital skills and knowledge and motivation as well as developing the communication skills of the learners. The study also highlighted some of the difficulties and challenges encountered while using digital tools in the English language classroom.